"You Say I'm Selling Phenol?" - Dow Chemical Company (1950)
Print advertisement for phenol, a chemical compound manufactured and sold by the Dow Chemical Company for a range of industrial applications including the production of plastics, dyes, antiseptics, and perfumes. The advertisement features an illustration of a lumber dealer holding a board of plywood. The accompanying text details how phenol is used in bonding agents applied to the plywood, among other uses. This advertisement appeared on page 43 of the January 9, 1950 edition of Time magazine.
Keywords: Chemical industry; Phenol; Dow Chemical Company; Corporations